2020
DOI: 10.1021/acsami.9b19712
|View full text |Cite
|
Sign up to set email alerts
|

Facial Amphiphilicity-Induced Polymer Nanostructures for Antimicrobial Applications

Abstract: New antimicrobial agents are needed to address ever-increasing antimicrobial resistance and a growing epidemic of infections caused by multidrug resistant pathogens. We design nanostructured antimicrobial copolymers containing multicyclic natural products that bear facial amphiphilicity. Bile acid based macromolecular architectures of these nanostructures can interact preferentially with bacterial membranes. Incorporation of polyethylene glycol into the copolymers not only improved the colloidal stability of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 59 publications
0
49
0
Order By: Relevance
“…Therefore, these differences in cell walls play a crucial role in the susceptibility of microbes to cationic polymers. Typically, Gram-negative and fungi are more difficult to eliminate than Gram-positive [9], but contrary behaviors have been proven for some cationic polymeric systems [10] and broad-spectrum antimicrobial polymers have also been developed [11][12][13]. Some studies concluded that cationic charge influences more the interaction with the bacterial membrane of Gram-positive bacteria in comparison with Gram-negative bacteria, while the hydrophobicity and amphiphilic balance of the polymers affects more the efficacy against Gram-negative bacteria [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, these differences in cell walls play a crucial role in the susceptibility of microbes to cationic polymers. Typically, Gram-negative and fungi are more difficult to eliminate than Gram-positive [9], but contrary behaviors have been proven for some cationic polymeric systems [10] and broad-spectrum antimicrobial polymers have also been developed [11][12][13]. Some studies concluded that cationic charge influences more the interaction with the bacterial membrane of Gram-positive bacteria in comparison with Gram-negative bacteria, while the hydrophobicity and amphiphilic balance of the polymers affects more the efficacy against Gram-negative bacteria [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a class of BA-based antibiotics termed Ceragenins have been prepared by covalently attaching amines to BAs, inspired by the molecular structure of squalamine, a naturally occurring aminosterol with potent antimicrobial activity, isolated from shark liver [101][102][103]. Similar molecules have been linked as pendants to polymers able to locally cluster the facial amphiphilicity of these cationic steroid antibiotics, thereby enhancing interactions with bacterial membranes [104][105][106] (Figure 3g-i). To date, BAs are actually used both as precursor and co-agent in drug formulation.…”
Section: Functionalized Bas In Medicinementioning
confidence: 99%
“…Pioneer studies suggest that amphiphilicity is one of the most important factors determining antimicrobial activity, cytotoxicity, and selectivity of SMAMPs 15 , 88 . Similar to AMPs, their amphiphilic nature enables SMAMPs to electrostatically interact with the bacterial membrane, whereas their hydrophobic moiety could intensify the interaction of peptidomimetics into the hydrophobic core of the bacterial lipid bilayer 41 , 89 . However, because less negatively charged lipids are found in the outer leaflet of the mammalian membrane than in the bacterial membrane, an excessive proportion of hydrophobic segments in SMAMPs will result in undesired hemolysis and deterioration of selectivity owing to a significant decrease in the charging effect 88 .…”
Section: Mdps and Their Mechanisms Of Actionmentioning
confidence: 99%